Intelligence Profile in Deliquent Adolescent (Study on Deliquent Adolescents in Correctional Institution for Male Children- Tangerang) - Naomi Soetikno; Stella Tirta (Department of Family and Consumer Sciences, Bogor Agricultural University, 2017)
Violence perpetrated by adolescents is very related with youth psychological conditions, one of which is intelligence aspect. Intelligence is an individual potency to be able to resolve problems logically, directed, and using ways that can be accepted by the environment. Through this study, we want to get the profile of the intelligence of juvenile perpetrators of violence who are now in correctional institution. The benefit of this study is to give an informations for parents and teachers to provide an appropriate parenting and education. This is a qualitatively study from four adolescent participants who commited violent crimes, aged 15-18 years, and they are residents of correctional institution for male children in Tangerang. Participants Intelligence was evaluated using Wechsler Intelligence Scale for Children (WISC) or Wechsler Belleveu (WB), and followed with interview of all participants. The study was conducted in February 2013 to May 2013. The Results show the full IQ scores of participants were in the category of Borderline Intellectual Functioning, with performance skills grew significantly than verbal skills. The Additional data about the participants was the participants were grew up in the families, which the parenting style of the parents or signficant persons accompanied by violence.